High temperature slagging gasification of municipal solid waste with biomass charcoal as a greener auxiliary fuel - Heberlein, Stephan (2022)
During high temperature slagging gasification of municipal solid waste (MSW), coal coke is typically used as an auxiliary fuel to maintain the high temperature in the gasifier and convert ashes into slag. Herein, biomass charcoal was utilized as a greener and more sustainable auxiliary fuel to replace the coal coke during stable and continuous gasification of MSW. Several monitoring characteristics were assessed, like operating conditions of the gasifier, influence of local MSW properties generated in Singapore, environmental impacts, and main by-products (slag, fly ash and metals). The performance data revealed that the replacement of coal coke with biomass charcoal provided significant environmental benefits. The use of biomass charcoal resulted in 78% less SO2 emissions, and 22% less generated fly ash because the lower sulfur content in biomass charcoal resulted in a 32% reduced use of sorbent for flue gas treatment. Furthermore, there was clear evidence of a 22% carbon footprint reduction due to replacing fossil fuel as auxiliary fuel. In addition, the slag characteristics demonstrated lower heavy metals leaching as compared to the incineration bottom ash generated from the conventional MSW incineration plant suggesting its great potential in the application as clean and green waste-derived material in the construction industry.